CONDENSATION, DESALINATION, AND WATER RECYCLING TO ENCOUNTER WATER STRESS - Rafika HELAIMIA (My University, 2023)
Abstract – Water is a gift of life from Allah. In Al-Quran, it is stated “And We sent down from the sky water (rain) in (due) measure, and We gave it lodging in the earth, and verily, We are able to take it away.” (1). Though water is indispensable for life and livelihoods, it is becoming a world-pressing societal and geopolitical critical issue, knowing that 800 million people worldwide cannot afford primary access to potable water and that nearly 2.2 billion people lack access to a safe water supply. As a result, freshwater scarcity is now the world's second most pressing concern, after the prompt population increment issue. If the problem of freshwater scarcity persists, ‘the world will miss water-related SDGs by a wide margin’; more than 40% of the world's population will be living in ever-seriously water-stressed regions by 2035 (2); ecosystems will become weakened and will be unable to meet population freshwater supply ; and developing countries will be the most affected, with 80% of their illnesses caused by a lack of access to water as well as poor water quality. To tackle the increased water shortage, reasonable water management methods are required. This article proposes three efficient sustainable water techniques for producing fresh water and thus meeting water scarcity's massive demand, along with their benefits and drawbacks. They are Condensation, desalination, and water recycling.
To tackle the increased water shortage, reasonable water management methods are required. This article proposes three efficient sustainable water techniques for producing fresh water and thus meeting water scarcity's massive demand, along with their benefits and drawbacks. They are Condensation, desalination, and water recycling.